2010
DOI: 10.1021/pr901079v
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Plasma from Patients Undergoing Coronary Artery Bypass Grafting Reveals a Protease/Antiprotease Imbalance in Favor of the Serpin α1-Antichymotrypsin

Abstract: We used proteomics to identify systematic changes in the plasma proteins of patients undergoing coronary artery bypass grafting (CABG) by means of cardiopulmonary bypass surgery. It is known that, after CABG, a complex systemic inflammatory responses ensues that favors the occurrence of adverse postoperative complications frequently recognizing inflammation itself and/or thrombosis as the underlying mechanism. We found a marked and persistent postoperative increase in the levels of the serpin-protease inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Downloaded from http://ahajournals.org by on April 27, 2019 Likewise, ACT was elevated during the first days after an acute coronary syndrome, 32,33 and a persistent postoperative increase was noticed after coronary artery bypass grafting. 34 Apart from this important role of ACT as a modulator between inflammation and progression of HF by extracellular mechanisms, it may also have important intracellular effects. ACT has the unique ability among serpins to bind to DNA, a property that is independent of its serine protease inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Downloaded from http://ahajournals.org by on April 27, 2019 Likewise, ACT was elevated during the first days after an acute coronary syndrome, 32,33 and a persistent postoperative increase was noticed after coronary artery bypass grafting. 34 Apart from this important role of ACT as a modulator between inflammation and progression of HF by extracellular mechanisms, it may also have important intracellular effects. ACT has the unique ability among serpins to bind to DNA, a property that is independent of its serine protease inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Equal amounts of proteins from mitral valve tissue from five subjects dissolved in urea buffer containing bromophenol blue were pooled together and 0.8% ampholytes pH 3–10 were added. 2‐DE was carried out on Protean IEF cell (Bio‐Rad, Milan, Italy) according to the manufacturer's protocol as previously described . For further details, please see Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The proteomic approach has been receiving much attention in this clinical area. Proteomic analyses of plasma taken from patients undergoing coronary artery bypass grafting with CPB revealed that a protease/antiprotease imbalance develops after surgery, with early activation of cathepsin G (a serpin involved both in inflammation and coagulation activation), and then a delayed increase in alpha 1-antichymotrypsin (an inhibitor of neutrophil cathepsin G) [ 55 ] (Table 3 ). This imbalance is consistent with the postoperative systemic inflammatory response and dysregulation of hemostatic balance.…”
Section: Cardiopulmonary Bypass Hypothermia and Remote Ischemic Prementioning
confidence: 99%